Modern food retailers and traditional markets in developing countries: Comparing quality, prices, and competition strategies in Thailand - Christin Schipmann; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2011)
Supermarkets and hypermarkets are expanding rapidly in many developing countries. While consequences for farmers and consumers were analyzed recently, little is known about the implications for traditional retail formats such as wet markets. Using data from a market survey in Thailand and hedonic regression models, we analyze quality and prices for fresh vegetables from different retail outlets. Compared to wet markets, modern retailers sell higher quality at higher prices, indicating that they are primarily targeting better-off consumers. Hence, they are not directly competing for the same market segments. Yet there are signs that modern and traditional markets will gradually converge.
Keywords: C21; L15; Q13; 330; supermarkets; modern retailers; traditional wet markets; product quality; vegetables; Thailand